MINWA : GAMBARAN NILAI KEHIDUPAN MASYARAKAT JEPANG - Yuliani Rahmah (IZUMI, 2017)
[Title: MINWA: The Reflection of Japanese society’s Life ] Folklore is part of a collective culture that is spread and passed down from generation to generation. In this paper we will discuss about the type of oral folklore that developed in Japan. This exposure focuses on an explanation of the values of life contained in all three. The values of life discussed include religious values, social values and moral values. By knowing these values can be known also things that became the origin of the formation of Japanese society identity. The results of this research is that folklor which in Japan known as Minwa, can be categorized into 3 types and knows as Shinwa, Densetsu and Mukashi Banashi. In the three types of folklore Mukashi Banashi is a type of folklore that is full of life values. In mukashi banashi the religious values, social values and moral values described not only in all the elements of the story builder, but they are expressed in more detail. gb777gb777slot gacorgb777gb777GB777GB777slot gacorslot gacor